Pengaruh Tata Kelola Perusahaan, Ukuran Perusahaan, Profitabilitas, dan Peluang Pertumbuhan pada Relevansi Nilai dari Penghasilan Akuntansi - Sebuah Studi di Bursa Efek Indonesia - Surinastiti Eka Putri; Rosinta Ria Panggabean (Ultima Accounting : Jurnal Ilmu Akuntansi, 2020)
Capital market serves as an alternative financing-wise and as a means investment-wise. Relevance of accounting information comes out as profound to investors as can be observed within the financial statements of a company. The aim of this study was to figure out the effects of corporate governance, firm size, profitability, and growth opportunities on the value relevance of accounting earnings. The present research used a quantitative method and secondary data in the form of annual reports, and the objects hired were 22 companies listed on the LQ45 index (August of 2018–January of 2019) of the Idonesia Stock Exchange for the period 2015–2017. Analysis was conducted by a descriptive statistical method. The results obtained showed that the variable profitability, which was measured on return on asset, affected the value relevance of accounting earnings, while the variables good corporate governance, firm size, and growth opportunities did not affect the value relevance of accounting earnings. Companies’ management is advocated to optimize the management of the assets in place as it was found in this research that return on asset had an effect on earnings response coefficient. This is necessary so that the companies are able to generate earnings response coefficients to which investors can respond positively. Keywords: Earnings Response Coefficient, Firm Size, Good Corporate Governance, Growth Opportunities, Indonesia, Return On Asset